Dampak Climate Changes Terhadap Pengelolaan Sumberdaya Air di Daerah Aliran Sungai (DAS) - Nabila, Nabila (WBS Laboratory, 2025)
Climate change has become a significant threat to water resources management in river basins (DAS). This article examines the impacts of climate change on water resources management, with a focus on changes in rainfall patterns, increasing temperatures, and effects on the hydrological cycle. Increased rainfall intensity and global temperatures have changed the characteristics of river discharge, affecting water availability for agriculture, households, and industry. Climate change also affects the hydrological cycle through changes in rainfall patterns, increasing temperatures, and changes in evapotranspiration. Studies have shown that increasing average temperatures and changing rainfall patterns in Indonesia have had significant impacts on water management in watersheds, including the Brantas and Citarum watersheds. In addition, land-use changes such as deforestation and urbanization exacerbate the impacts of climate change, increasing the risk of flooding and drought. Effective water resources management requires a holistic and adaptive approach, such as Integrated Water Resources Management (IWRM), which integrates various sectors and interests in water management. The implementation of IWRM in Indonesia has shown mixed results, with some watersheds successfully adopting this approach, while others face obstacles such as lack of coordination between agencies and limited accurate hydrological data. Innovative and participatory adaptive approaches to water management are needed to address challenges caused by climate change, ensure sustainability of water resources, and maintain ecosystem balance. This article emphasizes the importance of local community involvement and development of climate-resilient water infrastructure in water resource management in the basin